Impact of Basel III on the discretion and timeliness of banks’ loan loss provisions - Jutasompakorn, Pearpilai (2022)
The Basel III Accord tightens capital adequacy requirements for banks by increasing the minimum Tier 1 regulatory capital threshold from 4 to 6 percent. It also emphasizes the need to improve timeliness of loan loss provisions. Using a sample of European banks, we examine the impact of this regulation on banks’ discretionary loan loss provisioning behavior. Underscoring banks’ increased incentives to report higher capital ratios, we observe a post-Basel III increase in banks’ use of discretionary loan loss provisions (DLLPs) for capital management purposes and a corresponding reduction in the use of these provisions for income smoothing purposes. Moreover, we find that the timeliness of loan loss provisions has improved following Basel III. We also find that the post-Basel III increase in capital management behavior is greater for banks that do not face conflicting incentives when using DLLPs to improve Tier 1 versus total capital ratio. In contrast, the improvement in loan loss provisioning timeliness is greater for banks that are less likely to engage in capital management due to these conflicting incentives. Our findings suggest that Basel III has significantly altered banks’ discretionary loan loss provisioning behavior.